2012
DOI: 10.1002/j.1532-2149.2012.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy‐induced analgesia: a combined psychophysical and neurophysiological study

Abstract: In pregnant women, there is a progressive increase of heat pain threshold and a reduction of the CHEP amplitude, suggesting that a general inhibitory mechanism may be involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
2
21
0
1
Order By: Relevance
“…Our findings of no PIA effect with these static measures are in contrast with a study suggesting a progressive increase in heat pain threshold and a reduction of heat pain perception in pregnant women compared with nonpregnant subjects. 5 Our findings, however, support several studies showing no changes in static QST in pregnancy compared with postpartum. [3][4][5][6][7][8][9] Although CPM and mTS are reliable human experimental paradigms that measure dynamic components of pain modulation, 10,11,26 stability of these measurement tools repeated over prolonged time intervals as in this study is not well established.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our findings of no PIA effect with these static measures are in contrast with a study suggesting a progressive increase in heat pain threshold and a reduction of heat pain perception in pregnant women compared with nonpregnant subjects. 5 Our findings, however, support several studies showing no changes in static QST in pregnancy compared with postpartum. [3][4][5][6][7][8][9] Although CPM and mTS are reliable human experimental paradigms that measure dynamic components of pain modulation, 10,11,26 stability of these measurement tools repeated over prolonged time intervals as in this study is not well established.…”
Section: Discussionsupporting
confidence: 88%
“…Animal studies have demonstrated that gonadal hormones influence pain by modulation of the spinal cord dynorphin and κ opioid systems, [22][23][24][25] and that this phenomenon of pain inhibition can be abolished by blockade of spinal κ-opioid or δ-opioid receptors. 1 Although several animal studies studying PIA have shown significant pain modulation in the pregnant state, 1,2 studies evaluating PIA in women have used static QST, usually heat pain threshold and tolerance, [3][4][5] and have shown either no or a small effect. [3][4][5][6][7][8][9] Pain thresholds and tolerance may differ between animals and humans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations